Relevansi Kepemimpinan Eklesiastik Pentakostal di Era Kontemporer Suatu Pendekatan Pneomatokrasi - Tumbelaka, Josephine M; Marbun, Purim (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2025)
Hierarchical organizational frameworks. Such models are particularly vulnerable to the reality of spiritual degradation among both church leaders and congregations. In contrast, within a Pentecostal pneumatological perspective, leadership is understood as a manifestation of the Holy Spirit’s work, which is dynamic, active, inclusive, and transformative within the society, it cannot be separated from the spirituality of the Holy Spirit itself. This article aims to identify the relevance of the pneumatocratic leadership model, which positions the work of the Holy Spirit at the center of ecclesial leadership as the primary driving force across various aspects of life, with universal implications for society in the contemporary era. Utilizing a library research method, this article analyzes the characteristics and implications of pneumatocratic leadership as a transformational leadership model. The superiority of this pneumatological model lies in its charismatic, gift-based leadership within the church and the broader contemporare society. This article demonstrates that the pneumatocratic leadership model does not rely solely on structural power but is grounded in the guidance of the Holy Spirit, whose implications extend universally. Therefore, pneumatocratic leadership offers an alternative paradigm that is highly relevant for both the church and contemporary society in addressing the holistic challenges of pluralism, secularism, and the dynamics of global contemporare development.AbstrakKepemimpinan memiliki peran yang sangat signifikan dalam setiap organisasi. Perkembangan jaman mendorong munculnya fenomena gereja kekinian yang cenderung membentuk kepemimpinan gerejawi dibangun di atas hirarkisorganisatori semata, model ini cenderung rentan terhadap kenyataan degradasi spiritualitas pemimpin gereja dan jemaat.Sementara dalam perspektif Pentakostal pneumatologi, kepemimpinan dipahami sebagai manifestasi karya Roh Kudus yang hidup, aktif, inklusif, dan transformatif, tidak bisa terlepas dari spiritualitas Roh Kudus itu sendiri. Artikel ini bertujuan mengidentifikasi relevansi model kepemimpinan pneomatokrasi yang menempatkan pekerjaan Roh Kudus dalam kepemimpinan gereja sebagai pusat penggerak di berbagai aspek kehidupan yang berdampak bagi masyarakat secara universal di era kekinian. Melalui metode riset pustaka, artikel ini menganalisis karakteristik dan implikasi kepemimpinan pneomatokrasi sebagai model transformasional leadership yang menampilkan relevansi pneomatologi pada sifatnya yang relasional, berbasis karunia Roh (charismatic gift-based leadership di tengah perkembangan masyarakat kontemporer.Artikel ini menunjukan model kepemimpinan pneomatokratik tidak hanya bergantung pada kekuatan struktural semata, namun bersandar pada pimpinan Roh Kudus dimana implikasinya menjangkau secara universal dalam menghadapi tantangan pluralisme, sekularisme, serta dinamika perkembangan kontemporer global.